A capital role for the brain's insula in the diverse fibromyalgia-associated symptoms. (October 2020) - De Paepe, Boel; Smet, Joél; Baeken, Chris; Van Oosterwijck, Jessica; Meeus, Mira
Abstract: Unexplained yet persisting general and widespread non-articular musculoskeletal pain and the associated complaints, known as fibromyalgia (FM), is a common disorder with major social and economic impact. We postulate that in FM disturbance of neurotransmitter balances at the brain's insula not only leads to aberrant pain processing but could also govern other associated symptoms. Symptoms might arise from central nervous system dysregulation mediated through an imbalance between the excitatory neurotransmitter glutamate and the inhibitory transmitter gamma-amino butyric acid. The insula could also have a leading role in the dysregulation of heart rate and blood pressure, bladder and bowel symptoms, and anxiety and sleep disturbances which are experienced by many FM patients. The presented hypothesis explains how the diverse FM-associated symptoms could be linked, and puts the brain's insula forward as a possible therapeutic target to be further explored for FM.